Pengembangan Multimedia Flipbook Berbasis Augmented Reality untuk Meningkatkan Hasil Belajar pada Mata Pembelajaran IPAS Kelas IV Sekolah Dasar - Oscar Delano Sinaga; Akhmad Junaedi (Paedagogie, 2026)
Learning Natural and Social Sciences (IPAS) in elementary schools plays an important role in building students' conceptual understanding, but its implementation still faces obstacles such as low student engagement, limited media variety, and difficulties in visualizing abstract material. This study aims to develop a multimedia flipbook based on Augmented Reality and test its effectiveness in improving student learning outcomes. The method used is Research and Development (R&D) with the Borg and Gall  model which includes the stages of analysis, design, development, implementation, and evaluation. The study was conducted at Nongkosawit 02 Elementary School, Semarang with fourth-grade students as subjects. Data collection techniques included observation, interviews, questionnaires, and learning outcome tests, while data analysis used quantitative and qualitative descriptive approaches. The results of the study indicate that the multimedia flipbook based on Augmented Reality meets the criteria of validity, practicality, and effectiveness. The use of this media is able to increase student engagement and provide a more interactive and meaningful learning experience, thus impacting on improving IPAS learning outcomes. Thus, the developed media is worthy of being used as an innovative alternative in IPAS learning in elementary schools.